Impact of body mass index on overall survival in patients with metastatic breast cancer. (February 2021) - Saleh, Khalil; Carton, Matthieu; Dieras, Véronique; Heudel, Pierre-Etienne; Brain, Etienne; D'Hondt, Véronique; Mailliez, Audrey; Patsouris, Anne; Mouret-Reynier, Marie-Ange; Goncalves, Anthony; Ferrero, Jean Marc; Petit, Thierry; et al.
Abstract: Background: High Body mass index (BMI) is a risk factor for breast cancer among postmenopausal women and an adverse prognostic factor in early-stage. Little is known about its impact on clinical outcomes in patients with metastatic breast cancer (MBC). Methods: The National ESME-MBC observational cohort includes all consecutive patients newly diagnosed with MBC between Jan 2008 and Dec 2016 in the 18 French comprehensive cancer centers. Results: Of 22 463 patients in ESME-MBC, 12 999 women had BMI data available at MBC diagnosis. Median BMI was 24.9 kg/m 2 (range 12.1–66.5); 20% of women were obese and 5% underweight. Obesity was associated with more de novo MBC, while underweight patients had more aggressive cancer features. Median overall survival (OS) of the BMI cohort was 47.4 months (95% CI [46.2–48.5]) (median follow-up: 48.6 months). Underweight was independently associated with a worse OS (median OS 33 months; HR 1.14, 95%CI, 1.02–1.27) and first line progression-free survival (HR, 1.11; 95%CI, 1.01; 1.22), while overweight or obesity had no effect. Conclusion: Overweight and obesity are not associated with poorer outcomes in women with metastatic disease, while underweight appears as an independent adverse prognostic factor. Highlights: This is the first large multicenter cohort reporting BMI's effect on outcomes among patients with metastatic breast cancer. Overweight or obese status does not negatively influence outcome of metastatic breast cancer patients, whatever the subtype. Underweight is a strong negative independent prognostic factor on outcomes, whatever the subtype.